Promotion effect of proton-conducting oxide BaZr0.1Ce0.7Y0.2O3−δ on the catalytic activity of Ni towards ammonia synthesis from hydrogen and nitrogen. (13th September 2018) - Humphreys, John; Lan, Rong; Du, Dongwei; Xu, Wei; Tao, Shanwen
Abstract: In this report, for the first time, it has been observed that proton-conducting oxide BaZr0.1 Ce0.7 Y0.2 O3−δ (BZCY) has significant promotion effect on the catalytic activity of Ni towards ammonia synthesis from hydrogen and nitrogen. Renewable hydrogen can be used for ammonia synthesis to save CO2 emission. By investigating the operating parameters of the reaction the optimal conditions for this catalyst were identified. It was found that at 620 °C with a total flow rate of 200 mL min −1 and a H2 /N2  mol ratio of 3, an activity of approximately 250 μmol g −1  h −1 can be achieved. This is ten times larger than that for the unpromoted Ni catalyst under the same conditions although the stability of both catalysts in the presence of steam was not good. The specific activity of Ni supported on proton-conducting oxide BZCY is approximately 72 times higher than that of Ni supported on non-proton conductor MgOCeO2 . These promotion effects were suspected to be due to the proton conducting nature of the support. Therefore it is proposed that the use of proton conducting support materials with highly active ammonia synthesis catalysts such as Ru and Fe will provide improved activity of at lower temperatures. Graphical abstract: Image 1 Highlights: Proton conductor BaZr0.1 Ce0.7 Y0.2 O3−δ is a good promoter for ammonia synthesis. Catalytic activity of Ni-BaZr0.1 Ce0.7 Y0.2 O3−δ catalyst is 10 times of that for pure Ni. Catalytic activity of Ni-BaZr0.1 Ce0.7 Y0.2 O3−δ is 4 times of that for NiMgOCeO2 . Proton conductors are potential good promoters for ammonia synthesis catalysts.